2013
DOI: 10.3892/etm.2013.1120
|View full text |Cite
|
Sign up to set email alerts
|

Long-term facial nerve function following facial reanimation after translabyrinthine vestibular schwannoma surgery: A comparison between sural grafting and VII–XII anastomosis

Abstract: The aim of this study was to compare the recovery of long-term facial nerve function between patients who received sural grafts and those who underwent hypoglossal-facial anastomosis techniques following translabyrinthine vestibular schwannoma surgery. This study included 25 patients with vestibular schwannomas treated with translabyrinthine tumor removal. All patients had large tumors with a mean tumor size of 3.12 cm. Of these patients, six had progressive tumor enlargement symptoms and had been treated prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…9 Recent studies have shown that cable nerve graft interpositioning provides as good a result as a primary end-to-end coaptation. 2,17,47,50 However, the best possible postoperative outcome is HB Grade III, regardless of the graft material used or the technique employed, because the frontal muscle function rarely recovers and a certain degree of synkinesis is unavoidable after grafting. 2,30,39 The factors that could influence the results of FN reconstruction are discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Recent studies have shown that cable nerve graft interpositioning provides as good a result as a primary end-to-end coaptation. 2,17,47,50 However, the best possible postoperative outcome is HB Grade III, regardless of the graft material used or the technique employed, because the frontal muscle function rarely recovers and a certain degree of synkinesis is unavoidable after grafting. 2,30,39 The factors that could influence the results of FN reconstruction are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Delicate maneuvers of nerve approximation like peri-neurial, group funicular, and epineurial suturing are very difficult to perform in the depths of a pulsating CPA and even more so by a tired surgeon subsequent to a long and frequently laborious procedure. 50 Furthermore, the FN lacks a true fascicular organization until the geniculate ganglion, 2,8,9,29 and this makes it practically impossible to perform any kind of epi-or perineurial suturing until the geniculate ganglion. Hence, we prefer to use stitch-less fibrin glue for coaptation in the intradural and transdural anastomoses.…”
Section: Technique Of Reconstructionmentioning
confidence: 99%
“…The three patients who experienced less satisfactory outcomes had suffered from facial palsy for more than 1 year, consistent with a need for rapid surgical intervention. For the current methods of facial reanimation using the HN–FN end-to-end or ‘side’-to-end neurorrhaphy with or without a fresh nerve graft, the best possible outcome in a small proportion of patients is H-B grade III, and improvements are detected only after 6–12 months 4 20–24. Thus, our new surgical method, based on fundamental concepts and our own recent experimental results, represents a major advance in the rehabilitation of FN injury.…”
Section: Discussionmentioning
confidence: 99%
“…Since classic HN–FN end-to-end neurorrhaphy causes serious neurological deficits resulting from the sacrifice of the HN, surgical interventions have been improved by transferring half of the HN to the injured FN, either directly or via a nerve graft 4. However, clinical outcomes remain unsatisfactory and the postoperative recovery period is very long, sometimes beyond 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…• Despite morbidities such as synkinesia, sural graft techniques may show better improvement in facial nerve function than a CN XII to CN VII anastomosis at 1-and 3-year follow-up after surgery. 4 • In a successful facial nerve anastomosis, the typical recovery has the following trajectory 5 :…”
Section: Side Effectsmentioning
confidence: 99%